2022
DOI: 10.3389/fcell.2022.802699
|View full text |Cite
|
Sign up to set email alerts
|

Selective Retinoic Acid Receptor γ Antagonist 7C is a Potent Enhancer of BMP-Induced Ectopic Endochondral Bone Formation

Abstract: Bone morphogenetic proteins (BMPs) have been clinically applied for induction of bone formation in musculoskeletal disorders such as critical-sized bone defects, nonunions, and spinal fusion surgeries. However, the use of supraphysiological doses of BMP caused adverse events, which were sometimes life-threatening. Therefore, safer treatment strategies for bone regeneration have been sought for decades. Systemic administration of a potent selective antagonist of retinoic acid nuclear receptor gamma (RARγ) (7C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Systemic administration of an RARγ antagonist promoted BMP-induced ectopic bone formation in mice [52] . Furthermore, when 7C, a synthetic RARγ antagonist, was loaded into polylactide nanoparticles (NPs), local administration of 7C-NPs significantly increased BMP-induced bone formation in a murine ectopic bone formation model [54] . Histological analysis showed that 7C particularly enhanced cartilage formation in the early stage of BMP-induced endochondral bone formation.…”
Section: Bone Regeneration Drugs and Their Combined Effects With Bmpsmentioning
confidence: 99%
See 3 more Smart Citations
“…Systemic administration of an RARγ antagonist promoted BMP-induced ectopic bone formation in mice [52] . Furthermore, when 7C, a synthetic RARγ antagonist, was loaded into polylactide nanoparticles (NPs), local administration of 7C-NPs significantly increased BMP-induced bone formation in a murine ectopic bone formation model [54] . Histological analysis showed that 7C particularly enhanced cartilage formation in the early stage of BMP-induced endochondral bone formation.…”
Section: Bone Regeneration Drugs and Their Combined Effects With Bmpsmentioning
confidence: 99%
“…Thus, since BMP is a potent inducer of endochondral bone formation in vivo , an approach that assists cartilage formation would be useful for BMP-induced bone regeneration. In endochondral bone formation, the initially formed cartilage tissue serves as a template for bone replacement [54] , [55] , [56] . A larger cartilage template allows for larger bone regeneration [ 54 , 56 ].…”
Section: Bone Regeneration Drugs and Their Combined Effects With Bmpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone morphogenic protein (BMP) is known to activate mTORC1 and regulate cellular senescence [21][22][23] . A previous report showed that the transplantation of a BMP-containing collagen sponge allowed us to observe the bone formation capacity 24 . We hypothesized that the effects of osteoblast senescence would be enhanced by conditions of BMP-induced bone formation.…”
Section: Men1 Deletion Induces Osteoblast Senescence Attenuates Osteo...mentioning
confidence: 99%